"I love you as both and I love you as neither": Romantic partners' affirmations of nonbinary trans individuals. Issue 2 (3rd July 2019) - Galupo, M. Paz; Pulice-Farrow, Lex; Clements, Zakary A.; Morris, Ezra R.
Abstract: Background: Transgender microaffirmations are subtle endorsements of a person's gender identity through both verbal acknowledgements and behavioral gestures. Microaffirmations positively impact individuals who identify as transgender by acknowledging their gender identity and by communicating a sense of support and validation. Aims: This study focuses on microaffirmations specifically directed toward nonbinary transgender individuals within romantic relationships. Methods: Participants included 161 adults who identified as nonbinary: 85 who identified as gender nonconforming and 76 who identified as agender. These participants were either currently in a romantic relationship or had been in a romantic relationship within the past 5 years. Participants completed an online survey and provided examples of the microaffirmations they experienced from their romantic partners. Results: Responses were analyzed via thematic analysis, resulting in four overarching themes: (1) Identity Validations, acknowledgement and acceptance of nonbinary identity; (2) Identity Endorsements, active endorsements of nonbinary through language or behavior; (3) Active Learning, self-education about nonbinary identities; and (4) Active Defense, interruptions of others' negative actions directed at nonbinary partners. Discussion: Discussion of the results focuses on understanding how microaffirmations operate to complicate binary notions of gender/sex and positively influence nonbinary transgender individuals in interpersonal relationships.